Analytical approach of anchor rod stiffness and steel base plate calculation under tension. (February 2016) - Tsavdaridis, Konstantinos Daniel; Shaheen, Mohamed A.; Baniotopoulos, Charalampos; Salem, Emad
Abstract: The analysis of column base plate connections under biaxial moment or when large numbers of anchor rods are utilised is complicated. Such complex connections are regularly found in engineering practice, in spite of proposed, up-to-date finite element modelling techniques and analytical formulations being unsuitable. The lack of suitability arises from their development for non-practical column base plate idealised configurations. In the present paper, the results of a finite element study of single-headed anchors under tension are discussed, leading to the derivation of a simple equation that describes the stiffness of the headed anchor rod embedded in concrete. Furthermore, this paper suggests a simple and suitable approach to analyse base plate connections independent of loading scenarios, the number of anchor rods and their arrangement, taking into account the actual rigidity of the connection. In this study, a three-dimensional, nonlinear finite element model is developed through the use of the general-purpose finite element software package ABAQUS. The respective numerical results were verified against experimental ones. Highlights: Anchor rod stiffness and steel base plate under tension. Extensive parametric study using finite element analysis. Parameters: diameter of anchor plate and anchor rod, and length of anchor rod. Proposed equation represents the headed anchor bolts by mass-spring models. Calculated stiffness used to commercial available structural software.